The effect of perceived benefits,ease of use, and risk on culinary MSMEs’ interest in utilizing QRIS - Fitri Rahmawati; Santi Merlinda (Journal of Business & Banking, 2024)
The GNNT (National Non-Cash Movement) program is in line with fintech innovations that have a real impact on improving the efficiency of the payment system, financial inclusion, and the Indonesian economy. In the Kedungkandang sub-district area of Malang City, the number of culinary MSME units has increased, which can encourage GNNT to be realized. However, many culinary MSMEs have not optimized using QRIS as a non-cash payment tool. This study aims to see the effect of perceived benefits, ease of use, and risk on culinary msmes’ interest in utilizing QRIS. This research uses Quantitative method approach in this research. Culinary MSMEs are in Kedungkandang District, Malang City, as the research population. The sample was taken by a purposive sampling technique with a research sample of 100 respondents. Data ere collected by n distributing questionnaires and was measured using nominal and Likert scales-data processing with Stata 17 software with a multinomial logistic regression model. The results show that perceived benefits, convenience and risk partially affect the interest of culinary MSMEs in using QRIS. The perception of benefits, convenience and risk encourages an increase in the probability of interest in culinary MSMEs in using QRIS so that perceived benefits can increase MSME understanding of the benefits of QRIS, the perception of ease of use supports increased adoption of QRIS use; perceived risk can encourage strengthening the QRIS security system so that MSMEs are more confident and adopt QRIS.